An evaluation of positive behavioural support for children with challenging behaviour in community settings. (December 2018) - Grey, Ian; Mesbur, Maryann; Lydon, Helena; Healy, Olive; Thomas, Justin
This study employs a multiple baseline across individual design to describe the implementation of positive behavioural supports for seven children and adolescents in residential community settings over a period of 24 months. These individuals with intellectual disability are residing in one county with long-standing challenging behaviour resulting in home breakdown and serious physical injury. Four types of outcome are presented: rates of behaviour, rates of medication, psychiatric symptomatology and quality of life (QoL). Behaviours reduced to lower levels for the majority of participants following the implementation of positive behavioural supports, and improvements were largely sustained. The use of psychotropic medications reduced or stabilized for the majority of individuals over the same period. QoL Questionnaire scores improved substantially for four participants. The results are discussed in the context of a framework for supporting children with severe challenging behaviours in the community.